4y+6=-5

Simple and best practice solution for 4y+6=-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4y+6=-5 equation:



4y+6=-5
We move all terms to the left:
4y+6-(-5)=0
We add all the numbers together, and all the variables
4y+11=0
We move all terms containing y to the left, all other terms to the right
4y=-11
y=-11/4
y=-2+3/4

See similar equations:

| 10a+24=8a16 | | 8(-3x+1)=-23(×+1) | | 5x+5•X+1=35 | | 3+2x=-x/3-5/3 | | 2-(2x+6)=0 | | F(y+2)=-2y-3 | | 1/22c+4=-4 | | 0.5×2c+4=-4 | | x=26/99= | | 2n–13=9 | | 2y+13=73 | | 6x+12=0/3 | | 3=11–4n | | 6+12=b/3 | | -7x+5=8x+15 | | -18=-8c=6 | | 3z-4=31 | | 5(2x+3)-2=3x+5(x+1) | | 5(2x+3)-2=3x+5 | | 8x+3=−33+2x | | 4(3n+9)=16(2n+1) | | -10=20=+x | | 7(6-2n)=5(-3n+1) | | 7/r+-42=3/r-10 | | B²-7b=0 | | 2(4x-5=14) | | 15+9q=69 | | G(-2)+2=x+5 | | G(-2)+2=x+5x | | 2(x-1)=3=5x-3(2+x) | | 5+6=6-5t | | 10x-5-4(5x)=-65 |

Equations solver categories